The Intersection Between Illegal Fishing, Crimes at Sea, and Social Well-Being - Mackay, Mary; Hardesty, Britta Denise; Wilcox, Chris (Frontiers in Marine Science, 2020)
Illegal, unregulated, and unreported (IUU) fishing is a major contributor to global overfishing, threatening food security, maritime livelihoods, and fisheries sustainability. An emerging narrative in the literature posits that IUU fishing is associated with additional organised criminal activities, such as drug trafficking, human trafficking, slavery, and arms smuggling. We explored this narrative through a systematic literature review to identify the empirical evidence of association between illegal fisheries activities and organised crimes. Here we show that there is minimal evidence of organised crimes being linked to IUU fishing. Due to the covert nature of both organised crime and IUU fishing, we supplemented the literature review with analysis of media reports on illegal fishing from 2015-2019. We reviewed more than 330 individual media reports from 21 countries. From this database, less than 2% reported crimes associated with illegal fishing. The predominant associated crime mentioned were violations of worker’s rights, forced labour and/or modern slavery. We resolve the contradiction between the common narrative that fisheries and other crimes are linked by presenting three distinct business models for maritime criminal activities. These models offer an explanation to why certain crimes such as forced labour are associated with illegal fishing, while other crimes such as trafficking or smuggling are less likely to be linked to fishing activities. By disentangling these crimes from one another we can better focus on solutions to reduce illegal behaviour on the sea, protect those vulnerable to fisheries exploitation, and enhance livelihoods and social well-being.